A Preliminary Study: Esterification of Free Fatty Acids (FFA) in Artificially Modified Feedstock Using Ionic Liquids as Catalysts - Nurul Asmawati Roslan; Mohammad Haniff Che Hasnan; Norhayati Abdullah; Syamsul Bahari Abdullah; Sumaiya Zainal Abidin (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2016)
The exploration of non-edible oils as a feedstock has been positively affect the economic viability of biodiesel production. Due to the high level of free fatty acid (FFA) in non-edible oils, esterification is needed to remove the acidity to the minimum level before base-catalyzed transesterification. In this study, 1-hexyl-3-methylimidazolium hydrogen sulphate (HMIMHSO4) was self-synthesized and compared with the commercialized ionic liquid, 1-butyl-3-methylimidazolium hydrogen sulphate (BMIMHSO4). HMIMHSO4 and BMIMHSO4 were characterized by 1H NMR prior to use in the esterification reaction. The reaction was carried out in a batch reactor and variables such as types of alcohol, oil: alcohol molar ratio, temperature and types of stirring were investigated. The highest conversion for each catalyst was achieved using ethanol as a solvent at the condition of 343 K reaction temperature, 12:1 alcohol to oil ratio in 8 h reaction time. BMIMHSO4 showed higher conversion (98%) as compared to HMIMHSO4 with only 82% conversion. Clearly, BMIMHSO4 shows considerable potential to reduce the FFA in the feedstock as it is exhibit excellent catalytic activity due to lower alkyl chain of BMIMHSO4 compared to HMIMHSO4.